Analisis Rasio Keuangan Secara Cross Sectional Untuk Menilai Kinerja Keuangan Pada Perusahaan Sub Sektor Food And Beverage Yang Terdaftar Di Bursa Efek Indonesia Periode 2020 – 2022 - Salija Ridayati; Noviana Ramadhani; Rr Jihan Faadhilah Yuwandono; Vika Triya Wahyuni (BADAN PENERBIT STIEPARI PRESS, 2024)
This study aims to determine and compare the financial performance of Food And Beverage sub-sector companies listed on the IDX for the 2020-2022 period based on financial ratios, which include activity ratios, liquidity, solvency, profitability and market ratios. The method used in this research is descriptive analysis method with secondary data sources. The results showed that the financial condition of food and beverage sector companies listed on the Indonesia Stock Exchange in the 2020-2022 period was not good. This is indicated by the average value of financial ratios that are below the industry standard value. However, there are several companies whose financial conditions are quite good, even superior to other companies. These companies are ICBP, CAMP, and MYOR.